Application of Cinematography in the Development of Educational Choreography Creativity in Elementary Schools - Lora Gustia Ningsih; Amelia Hani Saputri; Agung Hero Hernanda (Universitas Negeri Semarang, 2025)
This study focuses on the application of cinematography in developing creativity in educational choreography at the elementary school level. The object of the research is the dance work Trash Craft, carried out at SDN 1 Segala Mider, Bandar Lampung, involving five female students from grades V and VI. The work raises the theme Zero Waste School as a form of children’s concern for the environment, particularly the issue of plastic waste. The research process went through several stages: movement exploration, improvisation, dancer selection, dance composition, filming, editing, and evaluation. Cinematography was employed not merely as a documentation tool, but also as a creative medium to strengthen the dance’s message through camera techniques, natural lighting, and audio-visual editing. The findings show that students were able to develop creativity in movement and expression, the Trash Craft dance successfully conveyed the message of environmental awareness, and cinematography proved effective in enhancing the aesthetics of the work as well as expanding the space for dance appreciation. Technical challenges such as differences in student ability and limited sound quality were resolved through creative solutions during practice and editing. This research emphasizes the relevance of integrating cinematography into dance learning as an innovative approach that is enjoyable, contextual, and aligned with the learning style of the digital generation.